Faktor-Faktor yang Berhubungan dengan Perilaku Ibu dalam Melakukan Kunjungan Antenatal Care (ANC) di Puskesmas Wae Codi Kabupaten Manggarai Tahun 2024 - Yustina Susanti; Masrida Sinaga; Tanti Rahayu (Yayasan Literasi Sains Indonesia, 2025)
Antenatal Care (ANC) is an effort to monitor the health of pregnant women and their fetuses to prevent complications during pregnancy. ANC visit behavior remains a challenge at the Wae Codi Public Health Center, Manggarai District. This study aims to analyze the relationship between factors such as maternal education level, residential distance, family income, family support, and health worker support on ANC visit behavior. This research employs an analytical observational method with a cross-sectional design. The sample consists of 75 mothers who gave birth in 2023, selected through purposive sampling. Data analysis was conducted using the chi-square test with α = 0.05. The results show significant relationships between education level (p = 0.001), residential distance (p = 0.000), family income (p = 0.000), and family support (p = 0.000) with ANC visit behavior. Highly educated mothers were more likely to utilize ANC services (64.3%) compared to mothers with low education levels (9.1%). Mothers living close to health facilities were more regular in visiting (40%) than those living far away (0%). Family income influenced visits, with financially well-off families utilizing ANC more frequently (34.7%) than low-income families (5.3%). Strong family support also increased ANC visits (37.3% vs. 2.7%). In contrast, health worker support showed no significant relationship (p = 0,093). These findings highlight the need for interventions such as education for mothers with low education levels, improved access to healthcare facilities, financial support, and strengthening the role of families to enhance ANC visits in the Wae Codi Public Health Center area.